2013
DOI: 10.1007/s13277-013-1460-1
|View full text |Cite
|
Sign up to set email alerts
|

MiR-495 regulates proliferation and migration in NSCLC by targeting MTA3

Abstract: Our previous studies have showed that metastasis-associated protein 3 (MTA 3) is overexpressed in non-small cell lung cancer (NSCLC) tissue, and increased MTA3 mRNA levels is a risk factor of lymph node metastasis. Using bioinformatics analyses, we found that MTA3 was a potential target of miR-495. However, the pathophysiological role of miR-495 and its relevance to the growth and development of NSCLC have yet to be investigated. The purpose of this study was to elucidate the molecular mechanisms by which miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…miR-495 is weakly expressed in prostate cancer and associated with prostate-specific antigen levels, lymph node invasion and Gleason scores (36). miR-495 is also downregulated in osteosarcoma (19), melanoma (20), endometrial cancer (21), acute myeloid leukaemia (22), renal cell carcinoma (37), breast cancer (38,39) and lung cancer (40,41). These findings suggested that miR-495 expression exhibits tissue specificity and may be a biomarker for these human cancers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…miR-495 is weakly expressed in prostate cancer and associated with prostate-specific antigen levels, lymph node invasion and Gleason scores (36). miR-495 is also downregulated in osteosarcoma (19), melanoma (20), endometrial cancer (21), acute myeloid leukaemia (22), renal cell carcinoma (37), breast cancer (38,39) and lung cancer (40,41). These findings suggested that miR-495 expression exhibits tissue specificity and may be a biomarker for these human cancers.…”
Section: Discussionmentioning
confidence: 96%
“…Lv et al found that restored miR-495 expression inhibits cell proliferation and motility and induces G0/G1 phase arrest in renal cell carcinoma (37). In lung cancer, miR-495 is involved in the regulation of cell proliferation, migration, epithelial-mesenchymal transition, chemosensitivity and chemoresistance (40,41,46). However, Tan et al indicated that miR-495 serves as an oncogene in bladder cancer through the regulation of cell proliferation and invasion (18).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the individual function of miR-410 and miR-495, a number of reports have linked both of these miRNAs to oncogenic pathways. Some studies have suggested a tumor suppressor role for these miRNAs (43)(44)(45), whereas others have indicated a pro-proliferative effect on tumor growth. Along these lines, miR-410 has been shown to be up-regulated in liver cancer and enhanced tumor cell growth (46).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that miRNAs participate in a broad range of biological processes, such as proliferation, apoptosis, invasion and metastasis of different kind of tumors [8]. MiR-495, as a tumor-suppressive miRNA in most cases, has been shown to be under-expressed and to repress various target genes to inhibit the malignant processes of several types of tumor [9,10]. However, there are different views on the role of miR-495 in regulating tumor invasion and migration.…”
Section: Introductionmentioning
confidence: 99%